A performance de técnicas estendidas a partir dos estudos Viola Spaces de Garth Knox e sua aplicabilidade na Sequenza VI de Luciano Berio - Martinez Galimberti Nunes (2013)
Written in 2009, the contemporary studies Viola Spaces, from composer and violist Garth Knox, arise in response to the gap in didactic teaching extended techniques. In his performance note, the author suggests that certain portion of the study no. 5 Rapid Repeat "[...] is a good preparation for Luciano Berio Sequenza VI of [...]."This statement motivated me to develop this research. Through an ascending line that starts with a literature review on the concept, history and performance of extended techniques, passes through the description of contemporary studies Viola Spaces and culminates in the Berio Sequenza VI which is approached their stylistic and technical- interpretative aspects.